Measurement of the cross section ratio sigma(t(t)over-barb(b)over-bar)/sigma(t(t)over-barjj) in pp collisions at root s=8 TeV - (:unkn) unknown (ELSEVIER, 2015)
The first measurement of the cross section ratio sigma(t (t) over barb (b) over bar)/sigma(t (t) over bar jj) is presented using a data sample corresponding to an integrated luminosity of 19.6 fb(-1) collected in pp collisions at root s = 8 TeV with the CMS detector at the LHC. Events with two leptons (e or mu) and four reconstructed jets, including two identified as b quark jets, in the final state are selected. The ratio is determined for a minimum jet transverse momentum p(T) of both 20 and 40 GeV/c. The measured ratio is 0.022 +/- 0.003 (stat) +/- 0.005 (syst) for p(T) > 20GeV/c. The absolute cross sections sigma(t (t) over barb (b) over bar) and sigma(t (t) over bar jj) are also measured. The measured ratio for p(T) > 40 GeV/c is compatible with a theoretical quantum chromodynamics calculation at next-to-leading order. (C) 2015 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.
Keywords: CMS; Physics; Top physics